Kadar Protein Dan Kualitas Tempe Koro Pedang DanBekatul Dengan Variasi Daun Pembungkus - Ratri, Hayu Purwaning; , Dra Titik Suryani M.Sc (2016)
Canavalia Tempe is tempe fermented with the addition of yeast form of mold or fungus Rhizopus sp. Rice bran has a fairly high protein content. Innovation canavalia tempe "koro pedang" and rice bran, banana leaves, hibiscus leaves and teak leaves. The purpose of this research to determine the levels of protein and quality tempe "koro pedang" and rice bran on the variation of leaf wrapper. The method used in this research is an experimental method by using a completely randomized design (CRD) two factors, one is the comparison "koro pedang" : bran (A0 = 200g : 0g, A1 = 180g : 20g, A2 = 170g : 30g and A3 = 160g : 40g) and factor 2 is leaf wrapper (B1 = banana leaves, B2 = leaf hibiscus and B3 = teak leaves. The results showed that the addition of bran and variation of leaf wrappers can affect the levels of protein canavalia tempe. Levels of proteins highest tempe on tempe treatment "koro pedang" 160g : 40g bran and teak leaf wrappers (A3B3) that is equal to 10.35 g / L. levels of protein in the treatment room tempe 200g lentils sword: 0g bran and hibiscus leaf wrappers (A1B2) that is equal to 4,2g / L. Quality canavalia tempeh and rice bran at different wrapper leaf produces a rather loud texture, aroma of fresh tempe-bit unpleasant and white colors average uneven until golden.